CHRONIC PRESSURE ULCERS IN TRAUMA AND NON-TRAUMA PATIENTS IN THE INTENSIVE CARE UNIT - Mrvaljevic, Milutin; Pajic, Srbislav; Radanovic, Drazen; Slijepcevic, Nikola; Jakovljevic, Sofija; Elboursh, Dusan; Bogosavljevic, Djurdjina; Cukic, Bojan; Sumanac, Milica (HEALTH CARE, 2023)
Introduction/Aim: Patients, who stay long in hospitals, nursing homes, and especially in intensive care units, are exposed to the risk of developing chronic wounds. The term “chronic wound” refers to wounds that do not heal despite all treatment measures taken in the period of six to eight weeks. The aim of this retrospective cohort study was to analyze data on chronic pressure ulcers that were collected in intensive care units (ICU) of the Urgent Care Center of the Clinical Center of Serbia during the five-year period, with the aim of determining the factors that influence their occurrence and healing.Methods: The retrospective cohort study was conducted from January 1st, 2018 to April 1st, 2023 at the Urgent Care Center of the University Clinical Center of Serbia in the intensive care units in polytrauma, neurosurgical and surgical patients. The study included 74 patients diagnosed with chronic pressure ulcers. Data for all participants were obtained from medical history and a list of discharges.Results: During in-hospital treatment in ICU, pressure ulcers were found in all 74 patients (56.8% of women and 43.2% of men), while combined chronic wounds were found in 57 (77.0%) patients. The largest number of these patients were elderly (70 and older) (31.1%) and with non-traumatic injuries (62%). All patients were tracheotomized with a gastrostomy tube placed. The localization of pressure ulcers was most often in the lumbosacral region (44.6%), followed by the trochanteric region (23.0%). The majority of patients had hypertension (90.5%), diabetes (79.7%), and chronic obstructive pulmonary disease (82.4%), while 28 patients (37.8%) died. 38 patients were underweight (51.4%), while 11 (14.9%) patients were overweight and obese.Conclusion: Risk factors for the occurrence of pressure ulcers should be evaluated at the moment of the first contact of the doctor with the immobile patient because this is the only prerequisite for timely prevention. Special emphasis should be placed on the elderly, underweight, and people with comorbidities.
Keywords: : pressure ulcers, intensive care, chronic wounds, risk factors